Influence of gluten and starch granules interactions on dough mixing properties in wheat (Triticum aestivum L.). (September 2020) - Gao, Xin; Tong, Jingyang; Guo, Lei; Yu, Liwei; Li, Shaopeng; Yang, Bingpeng; Wang, Libin; Liu, Yang; Li, Faji; Guo, Jun; Zhai, Shengnan; Liu, Cheng; et al.
Abstract: Wheat flour dough can be regarded as a complicated mixture in which gluten forms a continuous three-dimensional network filled with starch particles. Previous studies have concentrated on the influences of either gluten or starch alone on the rheological properties of wheat dough and found the components of gluten and starch responsible for the dough behavior, including use of parameters, such as the content of protein, wet gluten and amylose, for the evaluation of wheat quality. Earlier, in our study of six wheat materials, significant differences were observed in size distribution of starch granules affecting the dough mixing behavior. However, to our knowledge little research has been undertaken on the association of starch granules and protein networks on dough formation. In this study, the six wheat lines were further explored for the effect of gluten-starch interactions on dough properties. In order to achieve this, the wheat flour samples were quantified for gluten secondary structures, percentage of unextractable polymeric protein, high- to low-molecular-weight glutenin ratio, gluten micro-structure, number distribution of starch granules and moisture distribution in dough samples. A/Lacunarity (A-type starch granule content divided by lacunarity of gluten network) and B/A/Lacunarity (B- to A-type starch granule ratio divided by lacunarity) were proposed to characterize the level of interactions of differently sized starch granules to gluten protein networks in the dough. Results showed that dough stability time increased with the increase of B/A/Lacunarity, as closely packed dough, due to close interaction between starch granules and gluten, exhibited greater dough stability. Application of A/Lacunarity and B/A/Lacunarity as novel indicators is proposed to further elucidate precise influences between starch and gluten for better evaluation of dough properties. Graphical abstract: Image 1 Highlights: The micro-structure of starch and gluten in wheat dough was quantitatively analyzed. The physical interaction between starch and gluten in wheat dough was quantified. The filling degree of starch granules to gluten network in dough was determined. A/Lacunarity and B/A/Lacunarity are suggested as novel indicators for dough quality.